Measuring maturity in complex engineering projects - Silva Neto, Joao Carlos Araujo da 1976-; Coutinho, Italo 1976-; Teixeira, Gustavo 1976-; Moura, Alexandro Avila de (IGI Global, 2018)
"This book discusses the best way to promote this approach, when talking about complexity projects. It also proposes a model that will be adding additional important pillars to be applied over the measurement of complexity projects and investments"--